SISTEM KENDALI ALIRAN AIR MENGGUNAKAN PISTON WATER FLOW CONTROL SYSTEM USING PISTON - , ATHOUR ROKHIM, Budi Sumanto, S.Si., M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The use of control systems in the water filling into the water tank so play a lot in everyday life, especially in any buildings that use the water storage tank. Water flow control system using the latest breakthrough piston is very appropriate because the water flow from the lower leading to higher ground due to the encouragement of the piston. In compare charging into a holding tank above the poles need to be water flows from a higher place to the place of the lower. The advantages of this system is to use a hydraulic system in the filling because it uses fluid pressure as a power (power source) on a mechanism. In the hydraulic system needed power (power source) to make a pressurized fluid. The fluid then flows in accordance with the requirements or desired mechanism. Because the hydraulic system can result in a big moment with a small force. In the process easier because the storage tank is at the bottom of the house. If the water tank becomes dirty and can be cleaned easily save the cost installing of PVC.